2011
DOI: 10.1007/s12032-011-0015-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of colorectal cancer in the human immunodeficiency virus-infected African American population

Abstract: Colorectal Cancer (CRC) is the second leading cause of cancer mortality in the United States. African Americans (AAs) have the highest incidence of CRC of any American ethnic group. Survival from CRC in AAs is lower than in Caucasians, and the mean age of CRC development in AAs is younger. The AA community also has a high rate of HIV infection, accounting for 50.3% of all cases despite making up only 13.6% of the population. This retrospective cohort study identified 17 AA HIV patients with CRC. The patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…the uninfected controls had already presented with advanced stage colorectal cancer. Interestingly, the survival time was similar for both groups in this study [62].…”
Section: Colorectal Cancersupporting
confidence: 63%
See 1 more Smart Citation
“…the uninfected controls had already presented with advanced stage colorectal cancer. Interestingly, the survival time was similar for both groups in this study [62].…”
Section: Colorectal Cancersupporting
confidence: 63%
“…Kumar et al studied the clinical presentations of colorectal cancer in a retrospective study of 17 HIV-1-infected African Americans and 42 uninfected matched controls. The mean age of colorectal cancer diagnosis in the HIV-1-infected population was 50.70 versus 59.42 years in the control group [62]. Furthermore, 29.4% of the HIV-1-infected patients in this study were diagnosed with colorectal cancer at a younger age (<45 years) versus 6.35% for the control group.…”
Section: Colorectal Cancermentioning
confidence: 49%
“…Many studies have suggested that PLWH were more likely to be diagnosed with CRC, often at an earlier age or with a more aggressive malignancy (Patel et al, 2008; Berretta et al, 2009; Bini et al, 2009; Kumar et al, 2012; Wasserberg et al, 2007). However, many of these studies were single-center (Berretta et al, 2009; Wasserberg et al, 2007), and most did not adjust appropriately for age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies looking at colorectal cancer (CRC) risk in PLWH have been mixed. Some studies have shown that compared to HIV-uninfected individuals, PLWH may have worse survival (Berretta et al, 2009), more advanced disease at presentation (Bini, Green, & Poles, 2009), more neoplasms (Bini et al, 2009), a diagnosis at an earlier age (Kumar et al, 2012; Wasserberg, Nunoo-Mensah, Gonzalez-Ruiz, Beart, & Kaiser, 2007), or increased rates of CRC (Patel et al, 2008). Other studies have shown that PLWH either have no difference in incidence of CRC (Silverberg et al, 2011) or a lower incidence of CRC (Frisch et al, 2001; Engels et al, 2008; Silverberg et al, 2011; Van Leeuwen et al, 2009) than those without HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Prior reports of colorectal cancer in HIV + persons include case series, case–control studies, and a single retrospective multi-institutional study (10, 12, 13, 17). Similar to prior reports, case patients in the current study had an early onset of cancer (median 55 years) compared with population-based (Surveillance Epidemiology and End Results) estimates (median 69 years).…”
Section: Discussionmentioning
confidence: 99%